Character Education For Milenial Generation - Aisyah Aisyah; Sultan Ali; Wicaksono Wijaya (Proceeding International Seminar of Islamic Studies, 2019)
One thing that becomes a problem in the midst of too late people with this millennial era is the decline of the nation's character. Technological sophistication instead leads to dishonesty, arrogance, individualistic, materialistic and so on. That is why many people now complain about the differences in the character of children from the past with the millennial period. Ofcourse this condition becomes a difficult challenge for teachers to overcome, because on one hand the teacher must be able to ward off various possibilities arising from technological and information activities, but on the other hand the teacher also cannot forbid them to avoid it. Certainly not the same as character education in the past with character education today. This paper aims to analyze: (1) Urgency of character education in the millennial era, (2) Strategies for planting characters in students in the millennial era, (3) Challenges in planting characters in millennial generation. This study uses qualitative research methods using a descriptive analysis approach. Data collection techniques are done by observation, interviews, and study documentation. This research was conducted at MIS Hidayatussalam, for 2 months, and with a total of 10 informants. The results showed that: (1) Character education has urgency including building religious and nationalist personalities, creating a generation that is ready to face all kinds of challenges, creating a generation that is ready to face global competition, (2) Character investing strategies used among them through intra-curricular, co-curricular and extracurricular activities, (3) Some challenges faced are the lack of ability to filter the flow of globalization, the lack of collaboration between parents, educators, and society, the lack of exemplariness and habituation of adults.